2021
DOI: 10.1111/desc.13164
|View full text |Cite
|
Sign up to set email alerts
|

Children's long‐term retention is directly constrained by their working memory capacity limitations

Abstract: We explored the causal role of individual and age-related differences in working memory (WM) capacity in long-term memory (LTM) retrieval. Our sample of 160 participants included 120 children (6-13-years old) and 40 young adults (18-24 years). Participants performed a WM task with images of unique everyday items, presented at varying set sizes. Subsequently, we tested participants' LTM for items from the WM task. Using these measures, we estimated the ratio at which items successfully held in WM were recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 38 publications
6
35
0
Order By: Relevance
“…Our results replicate those of earlier findings in childhood development (Winsor et al, 2021), young adulthood (Wixted & Wells, 2017), and older adulthood (Colloff et al, 2017) documenting positive confidence-accuracy relations in LTM, albeit with variations in the strength of these relations across the lifespan (cf., Fandakova et al, 2013;Shing et al, 2009). Extending on these earlier studies, we found that similar confidence-accuracy relations arise in WM, the "gateway" through which new LTMs are formed (Forsberg, Guitard, Adams, et al, 2022;Forsberg, Guitard, & Cowan, 2021;Forsberg, Guitard, Greene, et al, 2022;Forsberg et al, 2023;Fukuda & Vogel, 2019;cf., Atkinson & Shiffrin, 1968;Cowan, 1988Cowan, , 2019Cowan et al, 2024). Moreover, the magnitude of the confidence-accuracy relation within an age group (i.e., the difference in recognition accuracy between lowest and highest confidence levels) was usually comparable in WM and in LTM, with rare exceptions.…”
Section: Discussionsupporting
confidence: 81%
“…Our results replicate those of earlier findings in childhood development (Winsor et al, 2021), young adulthood (Wixted & Wells, 2017), and older adulthood (Colloff et al, 2017) documenting positive confidence-accuracy relations in LTM, albeit with variations in the strength of these relations across the lifespan (cf., Fandakova et al, 2013;Shing et al, 2009). Extending on these earlier studies, we found that similar confidence-accuracy relations arise in WM, the "gateway" through which new LTMs are formed (Forsberg, Guitard, Adams, et al, 2022;Forsberg, Guitard, & Cowan, 2021;Forsberg, Guitard, Greene, et al, 2022;Forsberg et al, 2023;Fukuda & Vogel, 2019;cf., Atkinson & Shiffrin, 1968;Cowan, 1988Cowan, , 2019Cowan et al, 2024). Moreover, the magnitude of the confidence-accuracy relation within an age group (i.e., the difference in recognition accuracy between lowest and highest confidence levels) was usually comparable in WM and in LTM, with rare exceptions.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, the age-related LTM deficits observed in this study were modest; and only observed at supracapacity set sizes (4 and 6), leaving it open whether results would replicate in situations where larger age deficits are found. Interestingly, research using a very similar paradigm suggests that children’s WM limitations constrains their LTM performance in a similar way—but again, with less clear evidence at subcapacity set sizes (Forsberg et al, 2022). Nonetheless, these results have major potential implications, which we discuss next.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of new concepts and accumulation of information involves the manipulation of information and eventual storage into long-term memory, which requires information passing through working memory. Working memory has thus historically been viewed as a portal to long-term memory, particularly in early stages of development when learning is most important due to low levels of knowledge and automatized skills (Cowan, 2014;Forsberg et al, 2021). An individual with low working memory capacity will struggle to combine capacity, speed, knowledge, and strategies necessary for problem solving, inference making, and learning of complex skills and concepts (Alloway, 2006;Cowan, 2014;Halford et al, 1998;Reid, 2009).…”
Section: Education Learning and Child Developmentmentioning
confidence: 99%